African wild ass drinking behaviour on the Messir Plateau, Danakil Desert, Eritrea. (February 2021) - Tesfai, Redae T.; Parrini, Francesca; Owen-Smith, Norman; Moehlman, Patricia D.
Abstract: The critically endangered African wild ass ( Equus africanus ) occurs in the Danakil Desert of Eritrea and Ethiopia. Drinking behaviour and the costs of accessing water are critical to understanding how this threatened equid survives in an arid environment. Drinking data and distance travelled to water of 24 females and five males were recorded for 83 days during four study years. Drinking frequency per individual per water source was obtained by calculating the number of water visits of an individual per successive days of observation. The travel distance to water was estimated by measuring the distance between the morning foraging location and the water point. During the dry months, female African wild ass with young foals visited permanent water once a day, travelled on average 9 km and drank only at night. Non-reproductive adult females and males travelled to water every 5–10 days. In rainfall months, females with young foals drank twice a day and on average travelled 3 km to water, but dispersed up to 7 km from temporary water sources when livestock arrived annually. This spatial exclusion from water sources due to livestock presence may reduce female African wild ass ability to provide sufficient milk to their foals. Highlights: The African wild ass is listed as 'Critically Endangered' by the IUCN Red List (Moehlman et al., 2015).. The area is remote, extremely rocky and the climate is very hot. Asaila spring is the only available permanent water source. Access and travel distance to water is critical for lactating females to provide sufficient milk to their foals. It is therefore important to document the drinking behaviour of lactating African wild ass in relation to water sources. Information of this manuscript is vital for conservation efforts, of this species therefore it is important for publication.